[Im]Mobility and trucking disruption: what happened to isolated cities and individuals in Brazil after a supply blockage. Issue 2 (3rd April 2022) - Mello, Sérgio Carvalho Benício de; Bastos, Antonio Fagner de Silva; Mello, Gabriel Benício de
ABSTRACT: In May 2018, truckers paralysed Brazil producing a series of disruptions causing unprecedented immobility. The event was a logistical disaster, exposing major failures in commodity supply systems and causing monumental economic losses, cancellations of basic services, and the disruption of public services. In this paper, we approach this phenomenon by means of an urban study using the new mobilities paradigm and a dialectical character of social and spatial relations to help us understand what was going on. To accomplish this, we have performed content analysis of the virtual media during the trucking disruption and the 90 days that followed it. Our findings indicate that a paralysed society becomes disoriented and even aggressive when order, routine, and everyday life are disturbed. The paper concludes with notes about the consequences of immobility in daily life.